STUDENTS’ DIFFICULTIES IN SPEAKING COMPREHENSION OF VOCATIONAL HIGH SCHOOL STUDENTS - Panjaitan, Kurnia; Sihombing, Enita; Pasaribu, Clawdya Clintin; Siregar, Christina Anita Elizabeth (REVIEW OF MULTIDISCIPLINARY EDUCATION, CULTURE AND PEDAGOGY, 2022)
This research was made to describe the problems and difficulties of speaking to students at SMK GKPI 2 Pematangsiantar. This research used descriptive qualitative research. Researchers used questionnaire as technique to collect the data for this research. The results of this research indicate that students of SMK GKPI 2 Pematangsiantar have several problems and difficulties in speaking subjects. There are several obstacles and difficulties in practicing speaking, namely 1) the understanding about conversation; (2) lack of vocabulary; (3) pronunciation; (4) less confidence (5) worries about making grammar errors, (6) lack of technology, and (7) lack of motivation. Based on the data, the majority of students showed that vocabulary was the most problem in speaking skills.